Analysis of the Factors Affecting Community Income in Sondoang Village, Kalukku District, Mamuju Regency: Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Masyarakat Di Desa Sondoang Kecamatan Kalukku Kabupaten Mamuju - R, Irawan; H. Herman; Syarifuddin (Jurnal Actual Organization Of Economic, 2023)
The aim of the study was to determine the effect of the level of education, community employment and number of family members partially and simultaneously on income in Sondoang Village, Kalukku District, Mamuju Regency and to determine the dominant variable influencing people's income in Sondoang Village, Kalukku District, Mamuju District. This research is a descriptive research and data collection techniques were carried out by observation, interviews, questionnaires and documentation. Methods of data analysis using Multiple Linear Regression analysis. The results showed that the variable level of education, community employment and number of family members had a partial effect on the income of the people in Sondoang Village, Kalukku District, Mamuju Regency. The variables of education level, community employment and number of family members have a joint effect on community income in Sondoang Village, Kalukku District, Mamuju Regency and the education level variable that most dominantly influences community income in Sondoang Village, Kalukku District, Mamuju Regency because of the results Multiple Linear Regression analysis obtained the highest beta value of 5.215 with the lowest significant value of 0.000.